OPTIMASI HPMC DAN KARBOPOL DALAM FORMULASI SEDIAAN GEL ANTISEPTIK EKSTRAK ETANOL DAUN BELUNTAS DAN AKTIVITAS ANTIBAKTERI TERHADAP Staphylococcus aureus - Muhammad Dienulloh Qasyfur Rohman; Iwan Setiawan; Ardy Prian Nirwana (Jurnal Insan Farmasi Indonesia, 2020)
Beluntas leaf (Pluchea indica, L.) is one of the plants that has potential as an antibacterial, Where the leaves of Beluntas have several compounds, one of these is a flavonoid which has antibacterial activity. The aim of this research is to determine the optimum composition of HPMC and carbopol which will be formulated in the preparation of antiseptic gel ethanol extract of beluntas leaf using the SLD method. The extraction method used in this study is Maseration with ethanol as a solvent. Antiseptic gel manufacturing is done by optimizing the base of HPMC and Carbopol, Then testing the quality of the gel preparation and the results obtained that meet the requirements of the homogeneity, pH, dispersion, viscosity, consistency and stability test of the gel preparation. The optimum formula of antiseptic gel based on the simplex lattice design method is on a combination of a 4.5% HPMC base and a 0.5% carbopol. Antibacterial activity test found inhibition zone, this shows that the antiseptic gel preparation of the ethanol extract of beluntas leaves has the ability to inhibit against Staphylococcus aureus bacteria with an average diameter of the zone of inhibition by 17,66 mm.